Das Kampfgebiet zwischen Maas und Rhein in der Periode September 1944 bis März 1945 - Heemels, Jan (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Befreiung; Rhein-Maas-Gebiet; Soldat; Zweiter Weltkrieg

Het Duitslandbeeld en het Nederlandbeeld van scholieren in de grensregio - Pollemans, Robine (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Deutschlandbild; Euregio Rhein-Waal; Niederlandebild; Schüler; Schüleraustausch

The Bottom-Up Approach. Experiences with the Impact Assessment of EU and National Legislation in the German, Dutch and Belgian Cross-Border Regions - Unfried, Martin; Kortese, Lavinia Susan Josephine; Bollen-Vandenboorn, Anouk (Territorial Impact Assessment, 2020)
Aus den Verlagsangaben: „Considering the myriad cross-border regions that the EU counts, it is impossible for the European Commission to map detailed territorial cross-border effects in all of the EU’s border regions for the impact assessments it conducts. National governments also face obstacles when seeking to cohesively integrate cross-border impact assessments in the existing frameworks that they use to assess the impact of new legislative, policy and enforcement measures. Even border regions or cross-border entities themselves face challenges in implementing impact assessments in their own territories. Despite the need for structural analyses of the border effects of newly adopted legislation and legislation under review, in terms of policy and enforcement, there are issues regarding the availability of academic resources, relevant tools and know-how. For the last couple of years, researchers from Maastricht University have been assessing as a bottom up exercise the potential effects of legislative proposals on the specific Dutch/German and Dutch/Belgium cross-border territories. This article presents the methodology used and the experiences gained from 2016 to 2019 by highlighting a number of interesting cases. It also offers future ideas for conducting similar “bottom-up” regulatory territorial impact assessments in cross-border regions.“
Keywords: Euregio Maas-Rhein; Gesetzgebung; Grenzgebiet; Wirtschaftsbeziehungen; Wirtschaftsentwicklung

Die kartographiehistorischen Forschungen von Gerhard Aymans im Rhein-Maas-Gebiet - Krings, Wilfried (Entdeckungslandschaft Unterer Niederrhein - Land zwischen Maas und Rhein. Neue Forschungen zur Kulturlandschaft des Niederrheins auf der Grundlage der Arbeiten von Gerhard Aymans und Rudolf Straßer. Symposium im Kloster Graefenthal, Goch-Asperden, 2006, 2008)
Keywords: Historische Karte; Historische Kartografie; Kartografie; Niederrhein-Gebiet; Rhein-Maas-Gebiet

Die Bedeutung der Forschung von Prof. Dr. Gerhard Aymans für das niederländische Nordlimburg - Renes, Hans; Storms, Martijn (Entdeckungslandschaft Unterer Niederrhein - Land zwischen Maas und Rhein. Neue Forschungen zur Kulturlandschaft des Niederrheins auf der Grundlage der Arbeiten von Gerhard Aymans und Rudolf Straßer. Symposium im Kloster Graefenthal, Goch-Asperden, 2006, 2008)
Keywords: Historische Karte; Historische Kartografie; Kartografie; Kataster; Kleve (Kreis Kleve)

The border paradox. Uneven development, cross-border mobility and the comparative history of the Euregio Meuse-Rhine - Knotter, Ad (Fédéralisme Régionalisme, 2002)
Keywords: Euregio Maas-Rhein; Grenzverkehr

Westmünsterland - Ostniederlande. Entwicklung und Stellung eines Grenzraumes. Vorträge auf der Jahrestagung der Geographischen Kommission in Vreden 1983 - Geographische Kommission für Westfalen (Geographische Kommission für Westfalen, 1984)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2011/09/22/file_4/4295872.pdf
Keywords: Grenzgebiet; Münsterland (West); Niederlande (Ost)